Strategic Litigation in International Criminal Justice: Facilitating a View from Within. (28th February 2022) - Jeßberger, Florian; Steinl, Leonie
Abstract: This article inquires into strategic litigation in international criminal justice. Drawing on the findings of an empirical study, it sheds light on the practice and self-perception of Strategic Litigation NGOs (so-called SLiNGOs) who employ international criminal law not only as an advocacy tool but use litigation to target perpetrators of international crimes as part of a larger juridical–political strategy transcending the individual case. Following a brief reflection on the role and significance of NGOs in international criminal justice in general and an examination of the basic idea of strategic litigation, the article delves into an analysis of the concept of strategic litigation as employed by SLiNGOs as well as the various functions of strategic litigation specifically in the international criminal justice context. Relying on interviews with SLiNGO representatives, the authors examine whether SLiNGOs — in their self-perception — serve merely as 'assistant prosecutors' or rather as kickstarters, pacemakers and watchdogs of the enforcement of international criminal law. They further explore the counter-hegemonic potential of strategic litigation and SLiNGO's attitudes towards international criminal justice as such. Analysing potential pitfalls and critiques directed at strategic litigation and the responses of SLiNGOs to such criticisms, the authors conclude that strategic litigation can indeed fill a gap in the current state-based system of international criminal justice and suggest an agenda for further research.